A Cr-doped MAX phase coating, a preparation method thereof, a bipolar plate and a fuel cell
By depositing Cr-doped MAX phase coating on the surface of the substrate and subjecting electrochemical treatment, the problem of MAX phase coating prone to cracks after high temperature annealing in the prior art is solved, which improves the density and performance of the coating, and is suitable for mass production.
Patent Information
- Application Number
- CN202310156327.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-17
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-02-17
AI Technical Summary
The existing MAX phase coatings are prone to macroscopic cracks after high temperature annealing, poor density, low preparation efficiency, and are not conducive to mass production.
Using the preparation method of Cr-doped MAX phase coating, the Ta-Cr metal alloy layer, Ta-Cr-Al transition layer and Ta-Cr-Al-C composite layer were deposited on the surface of the substrate, and prepared by an improved magnetron sputtering vacuum furnace, and finally the coating was electrochemically treated to form a dense oxide film.
It improves the corrosion resistance, conductivity and mechanical strength of the MAX phase coating, reduces the impact of cracks after high-temperature annealing, and makes the coating self-healing ability and is suitable for mass production.
Smart Images

Figure CN116103625B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fuel cells, and in particular to a preparation method of a Cr-doped MAX phase coating, a bipolar plate and a fuel cell. Background Art
[0002] As one of the core components of fuel cells, the bipolar plate of a fuel cell is mainly responsible for the distribution of reactants and conduction of electricity as a component flow field structure. Therefore, in the corrosive solution environment of the fuel cell, the bipolar plate is required to have excellent conductivity, corrosion resistance and a certain mechanical strength. At present, metal bipolar plates are one of the most widely used fuel cell bipolar plates. Commonly used materials are aluminum, titanium and stainless steel. Usually, the most effective way to solve the conductivity and corrosion performance of metal bipolar plates in a corrosive environment is to coat the surface of the metal bipolar plate. Since the MAX phase has both the good corrosion resistance and mechanical strength of ceramics and the excellent conductivity of metals, it is the only choice as a coating material for metal bipolar plates.
[0003] Most of the existing MAX phase coatings deposit the MAX layer through PVD sputtering, and then form the MAX phase after vacuum thermal annealing. However, due to the recrystallization of the grains, grain growth, and increased internal stress of the MAX phase coating after high-temperature annealing, macro cracks in the MAX coating are generated, and ultimately the physical properties and anti-corrosion properties of the MAX phase coating deteriorate. At the same time, since vacuum thermal annealing often uses equipment such as high-temperature heat treatment furnaces, the processing temperature is high and the operation is cumbersome. During the annealing process, repeated feeding and vacuuming are required, which is time-consuming and labor-intensive, resulting in low preparation efficiency; and the existing methods usually directly use MAX phase targets when depositing the MAX layer, which is expensive and not conducive to the mass production of MAX phase coatings. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide a method for preparing a Cr-doped MAX phase coating, a bipolar plate and a fuel cell, so as to solve the problems of macro cracks, poor density, low preparation efficiency and disadvantages for mass production in the MAX layer in the prior art.
[0005] To achieve the above object, the first aspect of the present invention provides a method for preparing a Cr-doped MAX phase coating, comprising the following steps:
[0006] Providing a substrate and pre-treating the substrate;
[0007] A Cr-doped MAX phase coating is deposited on the surface of the pretreated substrate to obtain a Cr-doped MAX phase coating.
[0008] Furthermore, the step of depositing a Cr-doped MAX phase coating on the surface of the pretreated substrate specifically includes the following sub-steps:
[0009] Sputtering an M-Cr alloy target formed by a Cr-doped transition metal element M and a main group element target formed by a main group element A outside the M metal alloy layer to form a Cr-doped MA transition layer;
[0010] The X element target formed by C / N elements is sputtered outside the Cr-doped MA transition layer to form a Cr-doped MAX composite layer.
[0011] Furthermore, in the step of sputtering the Cr-doped MA transition layer outside the M metal alloy layer using the alloy target formed by the Cr-doped transition metal element M and the main group element target formed by the main group element A, a DC magnetron sputtering process is used to co-sputter to form the Cr-doped MA transition layer, and during sputtering, the sputtering power P of the M-Cr alloy target is M-Cr The sputtering power P of the main group element target A The ratio is: 2:1<P M-Cr :P A <3:1, the deposition time of the Cr-doped MA transition layer is 0.2-1h, and the deposition thickness of the Cr-doped MA transition layer is 50-300nm.
[0012] Furthermore, in the step of sputtering the X element target formed by the C / N element outside the Cr-doped MA transition layer to form a Cr-doped MAX composite layer, the deposition time of the Cr-doped MAX composite layer is 0.5 to 2 hours, and the deposition thickness of the Cr-doped MAX composite layer is 50 to 300 nm; the specific method of forming the Cr-doped MAX composite layer is:
[0013] The Cr-doped MAX composite layer is formed by co-sputtering using a medium frequency magnetron sputtering process, and during sputtering, the sputtering power P of the M-Cr alloy target is M-Cr Sputtering power P of X element target X The ratio is 0.5:1<P M-Cr :P X <2:1;
[0014] or
[0015] The Cr-doped MAX composite layer is formed by a reactive sputtering process, and during the reaction, X element gas is introduced into a magnetron sputtering vacuum furnace, and the flow rate of the X element gas is 10-15 cssm.
[0016] Furthermore, before the step of sputtering the M-Cr alloy target formed by the Cr-doped transition metal element M and the main group element target formed by the main group element A outside the M metal alloy layer to form the Cr-doped MA transition layer, the following steps are also included:
[0017] A Cr-doped M metal alloy layer is formed on the surface of the substrate by sputtering using an M-Cr alloy target formed by a transition metal element M doped with Cr.
[0018] Furthermore, in the step of sputtering the M metal alloy layer on the surface of the substrate using the M-Cr alloy target formed by the transition metal element M doped with Cr, a DC magnetron sputtering process is used to sputter the M metal alloy layer, and during sputtering, the composition ratio of the transition metal elements M and Cr in the M-Cr alloy target is 6.5:3.5<M:Cr<9.5:0.5, the deposition time of the M metal alloy layer is 0.2~1h, and the deposition thickness of the M metal alloy layer is 50~300nm.
[0019] Furthermore, in the step of depositing a Cr-doped MAX phase coating on the surface of the pretreated substrate to obtain a Cr-doped MAX phase coating, the Cr-doped MAX phase coating is prepared by using an improved magnetron sputtering vacuum furnace, and the improved magnetron sputtering vacuum furnace is provided with a three-stage cavity distributed in a linear manner, and the three-stage cavity includes a deposition chamber, a first annealing chamber and a second annealing chamber which are linearly arranged in the vacuum furnace.
[0020] Furthermore, after the step of depositing a Cr-doped MAX phase coating on the surface of the pretreated substrate to obtain the Cr-doped MAX phase coating, the following steps are also included:
[0021] The Cr-doped MAX phase coating deposited on the substrate is electrochemically treated to obtain a bipolar plate of the Cr-doped MAX phase coating, wherein the specific method of electrochemically treating the Cr-doped MAX phase coating is:
[0022] The substrate of the Cr-doped MAX phase coating is immersed in a dilute sulfuric acid solution, oxygen is introduced, and a preset voltage is applied to the Cr-doped MAX phase coating for a preset time, thereby completing the electrochemical treatment of the Cr-doped MAX phase coating and obtaining a bipolar plate of the Cr-doped MAX phase coating.
[0023] A second aspect of the present invention provides a bipolar plate of a Cr-doped MAX phase coating, comprising a substrate and a Cr-doped MAX phase coating formed on the surface of the substrate by the preparation method of the Cr-doped MAX phase coating as described above.
[0024] A third aspect of the present invention provides a fuel cell, comprising a bipolar plate having a Cr-doped MAX phase coating, wherein the Cr-doped MAX phase coating formed on the bipolar plate is prepared by the preparation method of the Cr-doped MAX phase coating as described above, or the bipolar plate is a bipolar plate having the Cr-doped MAX phase coating as described above.
[0025] The present invention prepares a Cr-doped MAX phase coating on the surface of a substrate. After the MAX phase coating is prepared, the MAX phase coating is electrochemically treated to promote oxidation of Cr elements in the MAX phase coating, thereby forming a dense oxide film on the MAX phase coating to improve the corrosion resistance of the MAX phase coating. At the same time, since the MAX phase coating is doped with Cr elements, when the Cr elements work in a corrosive environment, they can combine with oxygen to generate an oxidation reaction to form a dense oxide film on the MAX phase coating, seal cracks generated on the MAX phase coating after annealing, and reduce the influence of macro cracks caused on the MAX phase coating during high-temperature annealing on the corrosion resistance of the coating. After the doped Cr elements are oxidized, a dense and stable oxide film is generated, so that the MAX phase coating exhibits a self-healing ability, further improving the electrical conductivity, mechanical strength and corrosion resistance of the MAX phase coating.
[0026] In addition, the present invention also reduces the harsh process conditions of the MAX phase coating during the deposition process, and sequentially uses alloy targets, metal targets and carbon targets to form a MAX phase coating on the surface of the substrate by sputtering, co-sputtering and / or reactive sputtering, wherein the transition layer is formed by an MA alloy target formed by the main group element A and the metal element M doped with Cr, so that the elements have better bonding strength, and the formed MAX phase coating is more stable. At the same time, by improving the structure of the vacuum furnace equipment, the deposition process and the annealing process are carried out in the same equipment, which can effectively avoid the repeated entry and exit of the bipolar plate, reduce the process complexity, and shorten the process time. Moreover, based on the improved vacuum furnace equipment, the prepared MAX phase coating is annealed twice, and the temperature and time of a single annealing operation are reduced to avoid the generation of macro cracks in the MAX phase coating after high-temperature annealing, thereby further improving the conductivity, mechanical strength and corrosion resistance of the MAX phase coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0028] Figure 1 The present invention is a flowchart of a method for preparing a Cr-doped MAX phase coating according to an embodiment of the present invention.
[0029] Figure 2 for Figure 1 Flow chart of step S1 in FIG.
[0030] Figure 3 for Figure 1 Flowchart of step S2 in FIG.
[0031] Figure 4 This is a SEM image of a Cr-doped MAX phase coating prepared by the preparation method of the Cr-doped MAX phase coating of the present invention.
[0032] Figure 5 This is a SEM image of the MAX phase coating prepared using the comparative example method.
[0033] Figure 6 The present invention is a test curve diagram of a potentiodynamic test of a Cr-doped MAX phase coating prepared by the preparation method of the Cr-doped MAX phase coating of the present invention.
[0034] Figure 7 This is a test curve of the dynamic potential test of the MAX phase coating prepared by the comparative example method.
[0035] Figure 8 The present invention provides a test curve diagram of electrostatic potential test of a Cr-doped MAX phase coating prepared by the preparation method of the Cr-doped MAX phase coating of the present invention.
[0036] Fig. 9 The present invention is a corrosion current test curve of a Cr-doped MAX phase coating prepared by the preparation method of the Cr-doped MAX phase coating of the present invention. DETAILED DESCRIPTION
[0037] The following is further described in detail through specific implementation methods:
[0038] like Figure 1 As shown, a flow chart of a method for preparing a Cr-doped MAX phase coating provided by an embodiment of the present invention. In this embodiment, the MAX phase coating is mainly obtained by combining and depositing a metal element M, a main group element A, and a C / N element X. To further illustrate the present invention, this embodiment is described in detail by taking Ta as the metal element M, Al as the main group element A, and C as the X element as an example. The method for preparing a Cr-doped MAX phase coating of this embodiment specifically includes the following steps:
[0039] S1: providing a substrate 1 and pre-treating the substrate 1.
[0040] A substrate 1 is provided, and the surface of the substrate 1 is pretreated to remove organic matter, oil stains, and passivation films attached to the surface of the substrate 1 due to previous processing and cutting of the substrate 1, so as to improve the bonding strength of the MAX phase coating subsequently grown thereon and increase the reliability of the MAX phase coating.
[0041] like Figure 2 As shown, step S1 includes the following sub-steps:
[0042] S101: providing a metal substrate.
[0043] Specifically, a metal substrate is provided as a metal bipolar plate substrate, and the metal bipolar plate substrate is made of one or more of titanium, aluminum, and stainless steel metals to serve as a carrier for the growth of the MAX phase coating.
[0044] S102: Cleaning the surface of the metal substrate.
[0045] The metal substrate is ultrasonically cleaned and then air-dried for standby use to clean organic matter and oil stains attached to the surface of the metal substrate. When the metal substrate is air-dried, the metal substrate can also be dried to shorten the evaporation time of alcohol and acetone solution residues attached to the surface of the metal substrate, thereby shortening the entire process time.
[0046] S103: removing the passivation film on the surface of the cleaned metal substrate.
[0047] Since the surface of the metal substrate is in contact with air for a long time during storage, a passivation film will be formed on the surface of the metal substrate. Therefore, the passivation film needs to be removed before depositing the MAX phase coating. Specifically, the cleaned metal substrate is placed in a magnetron sputtering vacuum furnace, and the surface of the metal substrate is sputtered to remove the passivation film on the surface of the metal substrate. At the same time, under the impact of various ions, the surface of the metal substrate has a certain degree of roughness, thereby improving the surface activity of the metal substrate and the bonding performance of the surface, thereby increasing the bonding force between the subsequently deposited MAX phase coating and the surface of the metal substrate.
[0048] S2: depositing a Cr-doped MAX phase coating on the surface of the pretreated substrate 1 .
[0049] First, continue to place the substrate 1 in a magnetron sputtering vacuum furnace, and set the sputtering environment of the vacuum furnace so as to sputter and form a MAX phase coating on the surface of the substrate 1; specifically, after the magnetron sputtering vacuum furnace is evacuated, the substrate 1 is heated, and a bias voltage is introduced into the magnetron sputtering vacuum furnace, and the duty cycle and argon flow rate are adjusted and maintained; the temperature of the substrate 1 is maintained at 300-500°C, the bias voltage introduced is -200--70V, the duty cycle is 50-70%, and the argon flow rate is maintained at 25-70sccm. Then, a Ta-Cr metal alloy layer 2, a Ta-Cr-Al transition layer 3 and a Ta-Cr-Al-C composite layer 4 are sequentially deposited on the surface of the substrate 1 using a target material. Finally, after annealing, a Cr-doped Ta-Al-C system MAX phase coating is formed on the surface of the substrate 1.
[0050] During the deposition of the Ta-Cr metal alloy layer 2, the Ta-Cr-Al transition layer 3 and the Ta-Cr-Al-C composite layer 4 and the annealing treatment, all are carried out in the magnetron sputtering vacuum furnace in which the passivation film on the surface of the substrate 1 is cleaned in step S103. During the whole process, the substrate 1 does not need to be removed from the vacuum furnace, thereby avoiding the repeated vacuuming of the vacuum furnace due to the substrate 1 repeatedly entering and exiting the furnace, which can simplify the process flow and avoid contamination of each layer of coating after being removed from the vacuum furnace. The magnetron sputtering vacuum furnace is provided with a three-stage cavity distributed in a linear array, and the three-stage cavity includes a deposition cavity, a first annealing cavity and a second annealing cavity linearly arranged in the vacuum furnace. During the deposition of the MAX phase coating, the substrate 1 is translated in the vacuum furnace along the deposition chamber, the first annealing chamber and the second annealing chamber in sequence; specifically, the cleaned substrate 1 is deposited with a Ta-Cr metal alloy layer 2, a Ta-Cr-Al transition layer 3 and a Ta-Cr-Al-C composite layer 4 in sequence in the deposition chamber by setting corresponding deposition conditions, and then translated to the first annealing chamber for the first annealing treatment, and finally translated to the second annealing chamber for the second annealing treatment.
[0051] In this embodiment, by doping Cr into the transition metal element M, Cr has active chemical properties. During the working process, it can quickly combine with oxygen to undergo an oxidation reaction, thereby forming a dense oxide film on the surface of the substrate, which can repair the cracks generated on the MAX phase coating after annealing, thereby reducing the effect of macro cracks caused on the MAX phase coating during high-temperature annealing on the density of the coating, so that the MAX phase coating exhibits excellent corrosion resistance.
[0052] like Figure 3 As shown, step S2 includes the following sub-steps:
[0053] S201: sputtering a Ta—Cr metal alloy layer 2 .
[0054] Specifically, a DC magnetron sputtering process is adopted, and Ta-Cr alloy is used as a sputtering target to sputter a Ta-Cr metal alloy layer 2 on the surface of the substrate 1 to form a metal bond between the surface of the substrate 1 and the Ta element and / or the Cr element, so that the MAX phase coating prepared subsequently has good electrical conductivity. It is understandable that in some other embodiments, when sputtering a metal alloy layer on the surface of the substrate 1, other metal materials (such as transition metal elements such as Ti, Sc, and Nb) can also be doped with Cr to form a metal alloy layer by sputtering. Of course, the seed layer can also be formed by sputtering any one or more of the aforementioned transition metal elements and Ta and Cr.
[0055] During sputtering, the composition ratio of Ta and Cr in the Ta-Cr alloy target is 6.5:3.5<Ta:Cr<9.5:0.5, the deposition time of the Ta-Cr metal alloy layer 2 is 0.2~1h, and the deposition thickness of the Ta-Cr metal alloy layer 2 is 50~300nm. After sputtering is completed, the Ta-Cr alloy target is closed and the sputtering environment of the magnetron sputtering vacuum furnace is maintained.
[0056] S202: Sputtering Ta—Cr—Al transition layer 3.
[0057] Specifically, the substrate 1 sputtered with the Ta-Cr metal alloy layer 2 is kept in the deposition chamber, a DC magnetron co-sputtering process is adopted, and the Ta-Cr alloy and Al are used as sputtering targets, and a Ta-Cr-Al transition layer 3 is sputtered outside the Ta-Cr metal alloy layer 2 to form a weak covalent bond and a metallic bond between the Al element and the Ta element and / or the Cr element in the Ta-Cr metal alloy layer 2, so as to further increase the good electrical conductivity of the MAX phase coating prepared subsequently. It is understandable that in some other embodiments, when sputtering to form a transition layer, the Al target can also be replaced by other main group elements (such as Si, P, S, Ga, Ge, etc.) to form weak covalent bonds and metallic bonds between the main group elements and the transition metal elements of the metal alloy layer.
[0058] During sputtering, the Ta-Cr alloy target material still uses the alloy target material in step S201, and the ratio of the sputtering power of the Ta-Cr alloy target material to the sputtering power of the Al target material is: 2:1<P Ta-Cr :P Al <3:1(where P Ta-Cr is the sputtering power of Ta-Cr alloy target, P Al is the sputtering power of the Al target), the deposition time of the Ta-Cr-Al transition layer 3 is 0.2 to 1 h, the deposition thickness of the Ta-Cr-Al transition layer 3 is 50 to 300 nm, and after the sputtering is completed, the Ta-Cr alloy target and the Al target are closed and the sputtering environment of the magnetron sputtering vacuum furnace is maintained.
[0059] In this embodiment, the Ta-Cr-Al transition layer 3 is formed by sputtering a Cr-doped metal element M (i.e., a transition metal element) and a main group element Al as a target. Compared with the traditional method of forming a transition layer by using a metal element Cr and an X element (i.e., C or N), the Ta-Cr-Al transition layer 3 has better bonding strength, thereby improving the stability of the subsequently prepared MAX composite layer.
[0060] S203: Sputtering a Ta-Cr-Al-C composite layer 4.
[0061] Specifically, the Ta-Cr metal alloy layer 2 and the Ta-Cr-Al transition layer 3 sputtered are kept in the deposition chamber, a co-sputtering process is adopted, and Ta-Cr alloy, Al and carbon are used as target materials, and a medium-frequency magnetron sputtering carbon target is used to sputter a Ta-Cr-Al-C composite layer 4 outside the Ta-Cr-Al transition layer 3 to form a strong covalent bond and a weak ionic bond between the carbon element and the Ta element and / or the Cr element, so that the prepared MAX phase coating has high hardness, high melting point and good oxidation resistance and corrosion resistance; and the Ta-Cr-Al-C composite layer 4 formed by co-sputtering a carbon target with a Ta-Cr alloy and an Al target has few impurities in the film layer and stable quality, which can further improve the corrosion resistance. It is understandable that in some other embodiments, when sputtering the composite layer, the carbon target can also be replaced by a nitrogen element as a target material to form a strong covalent bond and a weak ionic bond between the nitrogen element and the transition metal element.
[0062] During sputtering, the sputtering power of the Al target is kept unchanged, and the carbon target is sputtered by a medium frequency power supply. The ratio of the sputtering power of the Ta-Cr alloy target to the sputtering power of the carbon target is 0.5:1<P Ta-Cr :P C <2:1(where P Ta-Cr is the sputtering power of Ta-Cr alloy target, P C is the sputtering power of the carbon target), the deposition time of the Ta-Cr-Al-C composite layer 4 is 0.5-2h, the deposition thickness of the Ta-Cr-Al-C composite layer 4 is 50-300nm, and after the sputtering is completed, the Ta-Cr alloy target, the Al target and the carbon target are turned off, the sputtering gas source and the bias are cut off, and the vacuum state is maintained.
[0063] In some other embodiments, the Ta-Cr-Al-C composite layer 4 can also be formed by a reactive sputtering process to improve the film forming rate and stability. Specifically, a carbon source gas (such as methane or acetylene, etc.) is introduced into a magnetron sputtering vacuum furnace, so that the carbon source gas bombards the Ta-Cr alloy target and the Al target during the sputtering process to produce a brilliant reaction to ionize carbon elements, which are then deposited outside the Ta-Cr-Al transition layer 3 to form a Ta-Cr-Al-C composite layer 4. When the Ta-Cr-Al-C composite layer 4 is formed by a reactive sputtering process, the flow rate of the carbon source gas is 10 to 15 cssm, the deposition time is 0.5 to 2 hours, and the deposition thickness is 50 to 300 nm.
[0064] S204: Annealing treatment.
[0065] The substrate 1 having the Ta-Cr-Al-C composite layer 4 formed thereon is subjected to annealing treatment to obtain a Cr-doped Ta-Al-C system MAX phase coating.
[0066] Specifically, the magnetron sputtering vacuum furnace is controlled to translate the substrate 1 deposited with the Ta-Cr-Al-C composite layer 4 from the deposition chamber to the first annealing chamber for the first annealing treatment. During the first annealing treatment, the annealing temperature is 500-700°C, and the first annealing time is 0.5-4h; after the first annealing treatment is completed, the magnetron sputtering vacuum furnace is continued to be controlled to translate the substrate 1 from the first annealing chamber to the second annealing chamber for the second annealing treatment. During the second annealing treatment, the annealing temperature is 600-800°C, and the second annealing time is 4-6h. At the same time, the total duration of the two annealing treatments is not less than 4.5h, so as to obtain a Cr-doped Ta-Al-C MAX phase coating having high hardness, high melting point, good oxidation resistance and corrosion resistance of ceramic materials and good electrical conductivity of metal materials.
[0067] As a preferred method of this embodiment, in order to increase the oxidation rate of the Cr element doped in the MAX phase coating and accelerate the formation of a dense oxide film, this embodiment further includes the following steps:
[0068] S3: electrochemically treating the coating.
[0069] The bipolar plate formed with the Cr-doped MAX phase coating after annealing is electrochemically treated to repair the cracks generated in the Cr-doped MAX phase coating during the annealing process, thereby making the Cr-doped MAX phase coating have a self-repairing function, thereby making the structure of the Cr-doped MAX phase coating denser, thereby further improving the corrosion resistance of the Cr-doped MAX phase coating.
[0070] Specifically, first, immerse the substrate 1 of the Cr-doped MAX phase coating in a dilute sulfuric acid solution; then, introduce oxygen into the dilute sulfuric acid solution; finally, apply a preset voltage to the Cr-doped MAX phase coating for a preset time to complete the electrochemical treatment of the Cr-doped MAX phase coating. During the electrochemical treatment, the pH value of the dilute sulfuric acid solution is 5 to 7, the flow rate of the oxygen introduced is 20 to 40 sccm, the voltage applied to the Cr-doped MAX phase coating is 0.4 to 0.8 V, and the immersion time is 0.5 to 12 hours.
[0071] The preparation method of the Cr-doped MAX phase coating of the present invention comprises the following steps: sequentially depositing a Ta-Cr metal alloy layer 2, a Ta-Cr-Al transition layer 3 and a Ta-Cr-Al-C composite layer 4 on a substrate 1, improving the process conditions during the deposition of the Ta-Cr metal alloy layer 2, the Ta-Cr-Al transition layer 3 and the Ta-Cr-Al-C composite layer 4, and performing an electrochemical treatment on the MAX phase coating after annealing, so that the MAX phase coating has a self-healing ability, and can reduce the macro cracks caused on the MAX phase coating during the high-temperature annealing process. The influence of density can improve the conductivity, mechanical strength and corrosion resistance of the MAX phase coating; at the same time, by improving the structure of the vacuum furnace equipment, the deposition process and the annealing process are carried out in the same equipment, which can effectively avoid the repeated entry and exit of the bipolar plate, reduce the process complexity, shorten the process time, and, based on the improved vacuum furnace equipment, the prepared MAX phase coating is annealed twice, and the temperature and time of a single annealing operation are reduced to avoid the generation of macro cracks in the MAX phase coating after high-temperature annealing, thereby further improving the conductivity, mechanical strength and corrosion resistance of the MAX phase coating.
[0072] Another embodiment of the present invention provides a bipolar plate of a Cr-doped MAX phase coating, and the bipolar plate of the Cr-doped MAX phase coating is realized based on the preparation method of the Cr-doped MAX phase coating. Specifically, the bipolar plate of the Cr-doped MAX phase coating includes a substrate 1 and a Cr-doped MAX phase coating deposited on the surface of the substrate 1. The Cr-doped MAX phase coating includes a Ta-Cr metal alloy layer 2, a Ta-Cr-Al transition layer 3 and a Ta-Cr-Al-C composite layer 4 deposited in sequence on the surface of the substrate 1; the Cr-doped MAX phase coating is prepared by the preparation method of the Cr-doped MAX phase coating, so that the bipolar plate can have both the high hardness, high melting point, good oxidation resistance and corrosion resistance of ceramic materials and the good electrical conductivity of metal materials.
[0073] In addition, another embodiment of the present invention also provides a fuel cell based on the preparation method of the above-mentioned Cr-doped MAX phase coating or a bipolar plate based on the above-mentioned Cr-doped MAX phase coating, wherein the fuel cell includes a bipolar plate formed with a Cr-doped MAX phase coating, and the Cr-doped MAX phase coating formed on the bipolar plate is prepared by the preparation method of the Cr-doped MAX phase coating as described above, or the bipolar plate is directly a bipolar plate with the Cr-doped MAX phase coating as described above. Of course, the fuel cell also includes other necessary components (such as battery cells, electrodes and other components) in addition to the bipolar plate, and the aforementioned necessary components can all adopt existing results, which will not be described in detail here. In this way, the bipolar plate of the fuel cell is prepared by the preparation method of the Cr-doped MAX phase coating of the present invention, so that the finally assembled fuel cell has stable electrochemical properties.
[0074] The preparation method of the Cr-doped MAX phase coating of the present invention is further described in detail below with reference to specific examples.
[0075] Example 1
[0076] The specific steps of the preparation method of the Cr-doped MAX phase coating of this embodiment are as follows:
[0077] S1': providing a substrate 1 and pre-treating the substrate 1.
[0078] Stainless steel is used as the substrate 1, and the surface of the substrate 1 is pretreated.
[0079] S101': Provide a stainless steel metal substrate.
[0080] Specifically, a metal substrate made of stainless steel is provided as a carrier for growing the MAX phase coating.
[0081] S102': Clean the surface of the stainless steel metal substrate.
[0082] The stainless steel metal substrate is immersed in alcohol and acetone solutions in turn for ultrasonic cleaning. After the cleaning is completed, the stainless steel metal substrate is taken out and dried for later use.
[0083] S103': removing the passivation film on the surface of the cleaned stainless steel metal substrate.
[0084] The cleaned stainless steel metal substrate is placed in a magnetron sputtering vacuum furnace, and an anode ion source is used and argon gas is introduced as a sputtering gas to sputter the surface of the stainless steel metal substrate, so that the argon gas is ionized and impacts the surface of the stainless steel metal substrate to remove the passivation film on the surface of the stainless steel metal substrate. At the same time, under the impact of each ion, the surface of the stainless steel metal substrate has a certain roughness, thereby improving the surface activity of the stainless steel metal substrate and the bonding performance of the surface, thereby increasing the bonding force between the subsequently deposited MAX phase coating and the surface of the stainless steel metal substrate. In this embodiment, when removing the passivation film, the flow rate of the introduced argon gas is preferably 10 sccm.
[0085] S2': A Cr-doped MAX phase coating is deposited on the surface of a pretreated stainless steel metal substrate.
[0086] The stainless steel metal substrate is then placed in a magnetron sputtering vacuum furnace, and the sputtering environment of the vacuum furnace is set so as to sputter and form a MAX phase coating on the surface of the stainless steel metal substrate.
[0087] Specifically, the magnetron sputtering vacuum furnace is evacuated, and the vacuum degree is preferably 5*10 -3 pa or less; then, the stainless steel metal substrate is heated and the temperature of the stainless steel metal substrate is ensured to reach 300°C, and at the same time, the bias switch of the magnetron sputtering vacuum furnace is turned on, and the sputtering bias is set to -70V and the duty cycle is set to 50%; finally, the flow rate of argon gas is set to 25sccm to provide a sputtering environment for the deposition of the MAX phase coating.
[0088] S201 ′: sputtering a Ta—Cr metal alloy layer 2 on the surface of the stainless steel metal substrate.
[0089] A Ta-Cr alloy target having a composition ratio of Ta to Cr of 7:3 was used for DC sputtering for 0.2 h to deposit a Ta-Cr metal alloy layer 2 with a thickness of 100 nm on the surface of the stainless steel metal substrate.
[0090] S202 ′: sputtering a Ta—Cr—Al transition layer 3 outside the Ta—Cr metal alloy layer 2 .
[0091] DC co-sputtering is performed using a Ta-Cr alloy target and an Al target with a sputtering power ratio of 2.5:1 for a sputtering time of 0.2 h to deposit a Ta-Cr-Al transition layer 3 with a thickness of 100 nm outside the Ta-Cr metal alloy layer 2.
[0092] S203 ′: sputtering a Ta—Cr—Al—C composite layer 4 outside the Ta—Cr—Al transition layer 3 .
[0093] The sputtering power of the Al target is kept unchanged, and a Ta-Cr alloy target and a carbon target with a sputtering power ratio of 1:1 are used for co-sputtering by a medium frequency power supply for a sputtering time of 0.5 h to deposit a Ta-Cr-Al-C composite layer 4 with a thickness of 100 nm outside the Ta-Cr-Al transition layer 3.
[0094] When sputtering the Ta-Cr-Al-C composite layer 4, if reactive sputtering is used, acetylene is introduced at a flow rate of 10 sccm and the sputtering time is 0.5 h to obtain a Ta-Cr-Al-C composite layer 4 with the same thickness as that obtained when medium-frequency sputtering of a carbon target is performed.
[0095] S204 ′: annealing the stainless steel metal substrate on which the Ta—Cr—Al—C composite layer 4 is deposited.
[0096] The stainless steel metal substrate deposited with the Ta-Cr-Al-C composite layer 4 is translated into the first annealing chamber, annealed at 600°C for 0.5h, and then translated into the second annealing chamber, annealed at 700°C for 4h to obtain a Cr-doped Ta-Al-C MAX phase coating.
[0097] Example 2
[0098] The difference between Example 2 and Example 1 is that after step S204', the Cr-doped Ta-Al-C system MAX phase coating is further subjected to electrochemical treatment. Specifically, Example 2 further comprises the following steps:
[0099] S3': electrochemical treatment of the Cr-doped Ta-Al-C system MAX phase coating.
[0100] A stainless steel metal substrate with a Cr-doped Ta-Al-C MAX phase coating attached to its surface was placed in a dilute sulfuric acid solution with a pH value of 7, and 20 sccm of oxygen was introduced. Then, a voltage of 0.6 V was applied to the Cr-doped Ta-Al-C MAX phase coating for 1 hour to complete the electrochemical treatment of the Cr-doped Ta-Al-C MAX phase coating.
[0101] Comparative Example 1
[0102] Comparative Example 1 is a comparative example of Example 1 and Example 2, and is different from Example 1 or Example 2 in that:
[0103] The specific method of forming the MAX phase coating by sputtering in Comparative Example 1 is as follows:
[0104] D101: After evacuating the vacuum furnace, turn on the bias switch of the vacuum furnace, set the sputtering bias to -70V and the duty cycle to 50%; finally, set the flow rate of argon gas to 25sccm.
[0105] D102: DC sputtering is performed using a Ta target for 0.2 h to deposit a Ta metal layer on the surface of a stainless steel metal substrate.
[0106] D103: DC co-sputtering was performed using a Ta target and an Al target with a sputtering power ratio of 2.5:1 for a sputtering time of 0.2 h to deposit a Ta-Al transition layer outside the Ta metal layer.
[0107] D104: Keeping the sputtering power of the Al target unchanged, Ta target and carbon target with a sputtering power ratio of 1:1 were co-sputtered by a medium frequency power supply for 0.5 h to deposit a Ta-Al-C composite layer outside the Ta-Al transition layer.
[0108] D105: After the vacuum furnace is vented, the stainless steel metal substrate with the Ta-Al-C composite layer deposited is taken out, placed in a high-temperature treatment furnace and vacuumized again for annealing. The annealing temperature is 800-1100°C. During the annealing process, the heating rate is 10°C / min, and the annealing treatment is performed for 4 hours when the best temperature is reached.
[0109] Example 3
[0110] The specific steps of the preparation method of the Cr-doped MAX phase coating of this embodiment are as follows:
[0111] S1": providing a substrate 1 and pre-treating the substrate 1.
[0112] Stainless steel is used as the substrate 1, and the surface of the substrate 1 is pretreated.
[0113] S101": Provide a stainless steel metal substrate.
[0114] Specifically, a metal substrate made of stainless steel is provided as a carrier for growing the MAX phase coating.
[0115] S102”: Clean the surface of the stainless steel metal substrate.
[0116] The stainless steel metal substrate is immersed in alcohol and acetone solutions in turn for ultrasonic cleaning. After the cleaning is completed, the stainless steel metal substrate is taken out and dried for later use.
[0117] S103”: Remove the passivation film on the surface of the stainless steel metal substrate after cleaning.
[0118] The cleaned stainless steel metal substrate is placed in a magnetron sputtering vacuum furnace, and an anode ion source is used and argon gas is introduced as a sputtering gas to sputter the surface of the stainless steel metal substrate, so that the argon gas is ionized and impacts the surface of the stainless steel metal substrate to remove the passivation film on the surface of the stainless steel metal substrate. At the same time, under the impact of each ion, the surface of the stainless steel metal substrate has a certain roughness, thereby improving the surface activity of the stainless steel metal substrate and the bonding performance of the surface, thereby increasing the bonding force between the subsequently deposited MAX phase coating and the surface of the stainless steel metal substrate. In this embodiment, when removing the passivation film, the flow rate of the introduced argon gas is preferably 10 sccm.
[0119] S2”: A Cr-doped MAX phase coating is deposited on the surface of a pretreated stainless steel metal substrate.
[0120] The stainless steel metal substrate is then placed in a magnetron sputtering vacuum furnace, and the sputtering environment of the vacuum furnace is set so as to sputter and form a MAX phase coating on the surface of the stainless steel metal substrate.
[0121] Specifically, the magnetron sputtering vacuum furnace is evacuated, and the vacuum degree is preferably 5*10 -3 pa or less; then the stainless steel metal substrate is heated and the temperature of the stainless steel metal substrate is ensured to reach 400°C, and at the same time, the bias voltage of the magnetron sputtering vacuum furnace is turned on to provide a sputtering environment for the deposition of the MAX phase coating.
[0122] S201": sputtering a Ta—Cr metal alloy layer 2 on the surface of the stainless steel metal substrate.
[0123] A Ta-Cr alloy target having a composition ratio of Ta to Cr of 8:2 was used for DC sputtering for 0.5 h to deposit a Ta-Cr metal alloy layer 2 with a thickness of 100 nm on the surface of the stainless steel metal substrate.
[0124] S202”: sputtering a Ta—Cr—Al transition layer 3 outside the Ta—Cr metal alloy layer 2.
[0125] DC co-sputtering is performed using a Ta-Cr alloy target and an Al target with a sputtering power ratio of 2:1 for a sputtering time of 0.5 h to deposit a Ta-Cr-Al transition layer 3 with a thickness of 100 nm outside the Ta-Cr metal alloy layer 2.
[0126] S203”: sputtering a Ta-Cr-Al-C composite layer 4 outside the Ta-Cr-Al transition layer 3.
[0127] Keeping the sputtering power of the Al target unchanged, a Ta-Cr alloy target and a carbon target with a sputtering power ratio of 1:1 are co-sputtered by a medium frequency power supply for 1 hour to deposit a Ta-Cr-Al-C composite layer 4 with a thickness of 100 nm outside the Ta-Cr-Al transition layer 33.
[0128] When sputtering the Ta-Cr-Al-C composite layer 4, if reactive sputtering is used, acetylene is introduced at a flow rate of 10 sccm and the sputtering time is 1 hour to obtain a Ta-Cr-Al-C composite layer 4 with the same thickness as that obtained when medium-frequency sputtering of a carbon target is performed.
[0129] S204”: annealing the stainless steel metal substrate on which the Ta-Cr-Al-C composite layer 4 is deposited.
[0130] The stainless steel metal substrate deposited with the Ta-Cr-Al-C composite layer 4 is translated into the first annealing chamber, annealed at 600°C for 1 hour, and then translated into the second annealing chamber, annealed at 700°C for 5 hours to obtain a Cr-doped Ta-Al-C MAX phase coating.
[0131] Example 4
[0132] The difference between Example 4 and Example 3 is that after step S204″, the Cr-doped Ta-Al-C system MAX phase coating is further subjected to electrochemical treatment. Specifically, Example 4 further comprises the following steps:
[0133] S3”: Electrochemical treatment of Cr-doped Ta-Al-C MAX phase coating.
[0134] A stainless steel metal substrate with a Cr-doped Ta-Al-C MAX phase coating attached to its surface was placed in a dilute sulfuric acid solution with a pH value of 7, and 30 sccm of oxygen was introduced. Then, a voltage of 0.8 V was applied to the Cr-doped Ta-Al-C MAX phase coating for 2 hours to complete the electrochemical treatment of the Cr-doped Ta-Al-C MAX phase coating.
[0135] Comparative Example 2
[0136] Comparative Example 2 is a comparative example of Example 3 and Example 4, and is different from Example 3 or Example 4 in that:
[0137] The specific method for forming the MAX phase coating by sputtering in Comparative Example 2 is as follows:
[0138] D201: After evacuating the vacuum furnace, turn on the bias switch of the vacuum furnace, set the sputtering bias to -90V and the duty cycle to 50%; finally, set the flow rate of argon gas to 35sccm.
[0139] D202: DC sputtering is performed using a Ta target for 0.5 h to deposit a Ta metal layer on the surface of a stainless steel metal substrate.
[0140] D203: DC co-sputtering was performed using Ta target and Al target with a sputtering power ratio of 2:1 for 0.5 h to deposit a Ta-Al transition layer outside the Ta metal layer.
[0141] D204: Keeping the sputtering power of the Al target unchanged, use a Ta target and a carbon target with a sputtering power ratio of 1:1 to co-sputter through a medium frequency power supply for 1 hour to deposit a Ta-Al-C composite layer outside the Ta-Al transition layer.
[0142] D205: After the vacuum furnace is vented, the stainless steel metal substrate with the Ta-Al-C composite layer deposited is taken out, placed in a high-temperature treatment furnace and re-evacuated for annealing. The annealing temperature is 800-1100°C. During the annealing process, the heating rate is 10°C / min, and the annealing treatment is performed for 5.5 hours when the best temperature is reached.
[0143] like Figure 4 and Figure 5 The figures are SEM images of a MAX phase coating doped with Cr prepared by the preparation method of the MAX phase coating doped with Cr of the present invention and a MAX phase coating prepared by the comparative example method. Figure 4 and Figure 5 It can be seen that the surface morphology of the Cr-doped MAX phase coating prepared by the preparation method of the Cr-doped MAX phase coating of the present invention is denser and has fewer cracks, and after electrochemical treatment, the density of the surface morphology of the Cr-doped MAX phase coating is significantly improved, the originally existing small cracks are also repaired, and the reliability is higher.
[0144] like Figure 6 and Figure 7 As shown in FIG. 1 , it is a test curve diagram of the dynamic potential test of the MAX phase coating doped with Cr prepared by the preparation method of the MAX phase coating doped with Cr of the present invention and the MAX phase coating prepared by the comparative example method. Figure 6 and Figure 7 It can be seen that the Cr-doped MAX phase coating prepared by the preparation method of the Cr-doped MAX phase coating of the present invention has a higher self-corrosion voltage, a smaller self-corrosion current density, and better anti-corrosion performance, and after electrochemical treatment, the self-corrosion voltage of the Cr-doped MAX phase coating is further improved, the self-corrosion current density is further reduced, and the anti-corrosion performance is also better.
[0145] like Figure 8 As shown in FIG. 1 , it is a test curve diagram of the electrostatic potential test of the Cr-doped MAX phase coating prepared by the preparation method of the Cr-doped MAX phase coating of the invention (the initial performance of the MAX phase coating prepared in the comparative example does not meet the test requirements); as Fig. 9 , which is a corrosion current test curve of the Cr-doped MAX phase coating prepared by the preparation method of the Cr-doped MAX phase coating of the present invention. Figure 8 and Fig. 9 It can be seen that the current density of the Cr-doped MAX phase coating prepared by the preparation method of the Cr-doped MAX phase coating of the present invention is still less than 5*10 -8 A / cm 2 , and after electrochemical treatment, the electrostatic potential test corrosion current density of the Cr-doped MAX phase coating is further reduced.
[0146] Therefore, it is shown that the Cr-doped MAX phase coating deposited by the method of the present invention has excellent corrosion resistance and good durability, meets the DOE requirements, and after electrochemical treatment, the Cr-doped MAX phase coating obtains a self-repairing function, so that the corrosion resistance and durability of the coating are further improved.
Claims
1. A method for preparing a Cr-doped MAX phase coating, characterized in that: The following steps are involved: Providing a substrate and pre-treating the substrate; The Cr-doped MAX phase coating is deposited on the surface of the pretreated substrate to obtain the Cr-doped MAX phase coating, wherein this step includes the following sub-steps: A Cr-doped MA transition layer is formed by sputtering an M-Cr alloy target formed by a Cr-doped transition metal element M and a main group element target formed by a main group element A outside the M metal alloy layer; wherein the Cr-doped MA transition layer is formed by co-sputtering using a DC magnetron sputtering process, and during sputtering, the sputtering power P of the M-Cr alloy target is M-Cr The sputtering power P of the main group element target A The ratio is: 2:1<P M-Cr :P A <3:1, the deposition time of the Cr-doped MA transition layer is 0.2-1h, and the deposition thickness of the Cr-doped MA transition layer is 50-300nm; The X element target formed by C / N element is sputtered outside the Cr-doped MA transition layer to form a Cr-doped MAX composite layer; wherein the deposition time of the Cr-doped MAX composite layer is 0.5-2h, and the deposition thickness of the Cr-doped MAX composite layer is 50-300nm; the specific method of forming the Cr-doped MAX composite layer is: The Cr-doped MAX composite layer is formed by co-sputtering using a medium frequency magnetron sputtering process, and during sputtering, the sputtering power P of the M-Cr alloy target is M-Cr Sputtering power P of X element target X The ratio is 0.5:1<P M-Cr :P X <2:1; or The Cr-doped MAX composite layer is formed by a reactive sputtering process, and during the reaction, X element gas is introduced into a magnetron sputtering vacuum furnace, and the flow rate of the X element gas is 10-15 cssm.
2. The method for preparing a Cr-doped MAX phase coating according to claim 1, characterized in that: Before the step of sputtering the M-Cr alloy target formed by the Cr-doped transition metal element M and the main group element target formed by the main group element A outside the M metal alloy layer to form the Cr-doped MA transition layer, the following steps are also included: A Cr-doped M metal alloy layer is formed on the surface of the substrate by sputtering using an M-Cr alloy target formed by a transition metal element M doped with Cr.
3. The method for preparing a Cr-doped MAX phase coating according to claim 2, characterized in that: In the step of sputtering the M metal alloy layer on the surface of the substrate using the M-Cr alloy target formed by the transition metal element M doped with Cr, a DC magnetron sputtering process is used to sputter the M metal alloy layer, and during sputtering, the composition ratio of the transition metal elements M and Cr in the M-Cr alloy target is 6.5:3.5<M:Cr<9.5:0.5, the deposition time of the M metal alloy layer is 0.2~1h, and the deposition thickness of the M metal alloy layer is 50~300nm.
4. The method for preparing a Cr-doped MAX phase coating according to claim 1, characterized in that: In the step of depositing a Cr-doped MAX phase coating on the surface of the pretreated substrate to obtain a Cr-doped MAX phase coating, the Cr-doped MAX phase coating is prepared by using an improved magnetron sputtering vacuum furnace, wherein the improved magnetron sputtering vacuum furnace is provided with a three-stage cavity distributed in a linear manner, and the three-stage cavity includes a deposition cavity, a first annealing cavity, and a second annealing cavity which are linearly arranged in the vacuum furnace.
5. The method for preparing a Cr-doped MAX phase coating according to claim 1, characterized in that: After the step of depositing a Cr-doped MAX phase coating on the surface of the pretreated substrate to obtain a Cr-doped MAX phase coating, the following steps are also included: The Cr-doped MAX phase coating deposited on the substrate is electrochemically treated to obtain a bipolar plate of the Cr-doped MAX phase coating, wherein the specific method of electrochemically treating the Cr-doped MAX phase coating is: The substrate of the Cr-doped MAX phase coating is immersed in a dilute sulfuric acid solution, oxygen is introduced, and a preset voltage is applied to the Cr-doped MAX phase coating for a preset time, thereby completing the electrochemical treatment of the Cr-doped MAX phase coating and obtaining a bipolar plate of the Cr-doped MAX phase coating.
6. A bipolar plate with a Cr-doped MAX phase coating, characterized in that: A method comprising: comprising a substrate and a Cr-doped MAX phase coating formed on the surface of the substrate; the MAX phase coating comprising a MA transition layer and a MAX composite layer; the MA transition layer is configured to form a Cr-doped MA transition layer by sputtering an M-Cr alloy target formed by a Cr-doped transition metal element M and a main group element target formed by a main group element A outside the M metal alloy layer; the MAX composite layer is configured to form a Cr-doped MAX composite layer by sputtering an X element target formed by a C / N element outside the Cr-doped MA transition layer; or The invention comprises a substrate and a Cr-doped MAX phase coating formed on the surface of the substrate by using the preparation method of the Cr-doped MAX phase coating according to any one of claims 1 to 5.
7. A fuel cell comprising a bipolar plate formed with a Cr-doped MAX phase coating, characterized in that: The Cr-doped MAX phase coating formed on the bipolar plate is prepared by the preparation method of the Cr-doped MAX phase coating as described in any one of claims 1 to 5, or the bipolar plate is a bipolar plate with a Cr-doped MAX phase coating as described in claim 6.
Citation Information
Patent Citations
Nanolaminated material, two-dimensional material and process for production of a material
US20190292106A1